Analisis Pengaruh Digital Finance terhadap Environmental, Social, dan Governance (ESG) dengan Green Innovation dan Environmental Information Disclosure sebagai Variabel Intervening: Studi pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2020-2024 - Nabila Khairunisa; Wisnu Mawardi (Diponegoro Journal of Management, 2026)
This study aims to analyse the effect of Digital Finance Innovation (DFI) on Environmental, Social, and Governance (ESG) performance, with Green Innovation (GI) and Environmental Information Disclosure (EID) as mediating variables, among banking companies listed on the Indonesia Stock Exchange during 2020–2024. The research used a quantitative approach with panel data regression analysis. The sample consisted of 21 banking companies selected through purposive sampling, yielding 105 observations. Data analysis was conducted using Stata 17 with a fixed-effects model (FEM), a Random-Effects Model (REM), and the Sobel Test. The results indicate that DFI has no significant effect on ESG, GI, or EID. Meanwhile, GI and EID have a positive and significant effect on ESG performance. The mediation test shows that GI does not mediate the relationship between DFI and ESG, whereas EID significantly mediates this relationship. These findings indicate that the implementation of digital finance in the Indonesian banking sector remains more oriented toward operational efficiency and administrative transparency than toward substantive sustainability transformation. This study contributes to the development of stakeholder legitimacy and digital transformation theories in explaining ESG practices within the banking industry.